Development of an integrated train driver performance model / Mohd Azlis Sani Md Jalil - Mohd Azlis Sani, Md Jalil (2015)

(untitled)
The purpose of this study was to develop an integrated performance model of train drivers. A human performance measure was developed, integrating several significant factors of the train driver, and a theoretical framework specified for train driver was established from an extensive review of the literatures. This framework formed the foundation of the study in order to understand the significant factors influencing the performance of a train driver. Three main domains of human, activity and context were proposed to represent the key indicators of the train driver's performance. The evaluation was conducted on train drivers of a major train operating company (TOC) in Malaysia, focusing only on drivers of intercity passenger trains and freight trains. 229 respondents had participated in the quantitative paper-and-pencil survey conducted, and the data obtained was subsequently analysed using SPSS software. An integrated framework was then tested using structural equation modelling (SEM)-PLS approach in theSmartPLS software to determine the relationship among the significant factors of train driver performance. Fourteen factors were hypothesized and tested under the three main domains, namely fatigue, job related tension (internal and external conflict), job satisfactions, occupational stress and sleepiness, which were grouped under human domain; while driving task and job demand represented the activity domain; and lastly, the context domain consisted of the working condition, safety culture, safety issue, working environment and work facilities. The results indicated that fatigue, job related tension (internal conflict) and occupational stress; under human domain were found to be the significant factors which influence the performance of train drivers. For the activity domain, hypothesis testing proved that driving task, was significant factor. In the context domain; three factors were found to be significant. These include safety culture, working environment and iv working condition. To summarize, the study identified a total of seven significant factorswhich include occupational stress, job related tension – internal conflict, fatigue, driving task, work environment, safety culture and working condition. However, the results have failed to support the remaining seven factors of job related tension (external conflict), job satisfactions, sleep, job demand, work facilities, and safety issue. Significant to this research was that an integrated Malaysian train driver performance model has been successfully developed for identifying the significant factors that influence train driver performance, highlighting the interaction between human factors, human activities and its context. Through this approach, this study has looked at the significant factors in holistic and comprehensive perspective without ignoring other potential domains of factors. Therefore, this model would benefit the rail industry by assisting them in identifying the factor(s) That require close observation and improvement. Thus, the overall performance of the industry would be upgraded and contributes to the betterment of the system and the rail industry.